International trade, trade policy, and the WTO - JIN, Wei (Institutional Knowledge at Singapore Management University, 2018)
This dissertation comprises three papers that study the welfare impact of GATT/WTO, the effects of preference bias on trade flows and welfare, and the optimal trade policy with strategic interactions under a Ricardian model. The ﬁrst chapter provides a comprehensive evaluation of the welfare impact of GATT/WTO in its entire history of 1950-2015 for 180 countries. The analysis embeds non-parametric matching methods in structural quantitative simulations. The results indicate substantial (but highly heterogeneous) welfare gains created by GATT/WTO at the global level and across more than six decades of its history. An extensive set of robustness checks with respect to model speciﬁcations, parameter values, and matching estimations are provided. We also characterize the effects of GATT/WTO on global income disparity, its interaction with preferential trade agreements, and the effects of China‘s WTO entry. The second chapter estimates the effects of bilateral and time-varying preference bias on trade flows and welfare. We use a unique dataset from the BBC World Opinion Poll that surveys (annually during 2005-2017 with some gaps) the populations from a wide array of countries on their views of whether an evaluated country is having a mainly positive or negative inﬂuence in the world. We identify the effects on bilateral preference parameters due to shifts in these country image perceptions, and quantify their general equilibrium effects on bilateral exports and welfare (each time for an evaluated exporting country, holding the exporting country's own preference parameters constant). We consider ﬁve important shifts in country image: the George W. Bush effect, the Donald Trump effect, the Senkaku Islands Dispute effect, the Brexit effect, and the Good-Boy Canadian effect. We ﬁnd that such changes in bilateral country image perceptions have quantitatively important trade and welfare effects. The negative impact of Donald Trump’s “America First" campaign rhetorics on the US' country image might have cost the US as much as 3% of its total exports and gains from trade. In contrast, the consistent improvement of Canadian country image between 2010 and 2017 has amounted to more than 8% of its total welfare gains from trade. The third chapter incorporates strategic interactions into a canonical Ricardian model where two countries choose their optimal trade taxes. We show that in a Nash equilibrium, a country's optimal import tariffs are zero, whereas the optimal export taxes are weakly increasing with respect to its comparative advantage. Compared with Costinot, Donaldson, Vogel, and Werning (2015) where Foreign is passive, the structure of optimal trade policy with strategic interactions remains the same, but the welfare gain from trade policy for each country is lower. When Foreign is active, the welfare gain for Home from its trade policy is smaller because Foreign also exerts its market power on its exported goods over Home's consumers.